Pengembangan Alat Peraga Praktikum Efek Doppler Menggunakan Sensor FC-04 Dan Arduino Uno Di SMA - Jannah, Adelia Raudhatul; Hamdani, Dedy; Medriati, Rosane (Jurnal Penelitian Pembelajaran Fisika, 2023)
This study aims to produce products in the form of practicum props using FC-04 and Arduino uno sensors on Doppler effect materials in SMA. Knowing the feasibility of the practicum props developed, as well as to find out the student’s perception of the practicum props developed. This research is a type of development research (Research and Development) with the development model used, namely the ADDIE model, namely Analysis, Design, Development, Implementation, and Evaluation. Validation of props was carried out by 3 media experts and 3 material experts. To assess the products developed from the aspects of tool efficiency, tool durability, aesthetics, accuracy, safety for students, aspects of linkage to learning materials, and content in educational values. The results of the media and material validation tests obtained average results of 92.36% each with a very decent category and 79.17% with a decent category. Based on these results, it can be concluded that Doppler effect practicum props using FC-04 and Arduino uno sensors are feasible. As for the perception results, students get an average result of 78.45% with a good category.Keywords: Props, Arduino Uno, Doppler Effect